(untitled) (Veterinary Science, 2019)
Osteopontin (OPN) is the most abundant non-collagen protein in the bone matrix, where it fulfils the function of cellular adhesion and biomineralization. In the present work, the authors report the temporal and spatial localization of OPN during the repair of experimental orthopaedic bone defects treated with demineralized bone matrix (DBM) processed by the authors. 30 rabbits were used, which were given an orthopaedic bone defect of critical size in one of the radiuses, which was filled with DBM. The rabbits were euthanized in groups of 5 individuals at days 7, 15, 21, 30, 60 and 150. Histological cuts were immunomarked to establish the spatial and temporal immunomarcation of OPN. The histological cuts were observed with an optic microscope with which histological images were captured and analysed with the ImageJ software. The image analysis allowed the authors to establish the optic density (OD) and the integrated optic density (IOD). The data was analysed with the ANOVA and Fischer LSD tests. At day 7, the presence of OPN was observed only in the DBM particles, where the OD was 0.08 and the IOD was 1.64; at day 15, OPN marked different sites of collagen condensations and cells contained in the interior of the matrix. In this period the OD was 0.096 and the IOD, 9.26. At days 21 and 30, the OPN immunosignalled osteocytes, osteoblasts, osteoclasts and hypertrophic chondrocytes in the bone trabeculae adjacent to the ossification zones. At day 21 the OD was 0.17 and IOD 6.22. At day 30, the OD was 0.14 and the IOD 2.52. At days 60 and 150, OPN was evenly distributed in the new bone matrix with an OD: 0.10 and IOD: 0.48, and OD: 0.35 and IOD: 3.80, respectively. The OD and IOD showed significant differences (p<=0.05) between days 7, 15, 21 and 30; and there was no difference at days 60 and 150 (p=0.05). OPN was found in the DBM particles: it increased the optic densities at day 15 and it diminished at day 60, after which it increased the OD and IOD again until day 150. It was established that the OPN immunoexpressed during the repair process in indifferentiated cells, osteoprogenitor chondrocytes and osteoblasts. The variation of OD and IOD allowed the authors to establish that the greatest degree of immunoexpression of OPN was at day 15 after repair initiated. On the other hand, the increase registered between days 60 and 150 post treatment was due to the biomineralization of the bone matrix.